2014
DOI: 10.1186/1472-6882-14-479
|View full text |Cite
|
Sign up to set email alerts
|

Studies on antidiarrhoeal, antispasmodic and bronchodilator activities of Operculina turpethum Linn

Abstract: BackgroundTraditionally, Operculina turpethum has been used in a wide range of ailments such as, gastrointestinal disturbances and asthma. It is found in China, South Asia, Pacific Islands, and Australia. This study was aimed to provide a possible pharmacological basis for the medicinal use of O. turpethum in gut and airways disorders.MethodsCastor oil-induced diarrhoeal mice model and isolated tissue preparations such as, rabbit jejunum and guinea-pig tracheal preparations were used to test the antidiarrhoeal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…In folkloric medicine, its roots, stems, and leaves are used in wide range of ailments including gastrointestinal disorders, anemia, asthma, obesity, paralysis, and pain. [12][13][14] Previous reports have shown that O. turpethum possesses hepatoprotective, antiulcer, antidiabetic, and anti-inflammatory activities. 13,15,16 This study was aimed at the evaluation of the analgesic and antioxidant activities of the methanolic extract of O. turpethum in mice.…”
Section: -10mentioning
confidence: 99%
“…In folkloric medicine, its roots, stems, and leaves are used in wide range of ailments including gastrointestinal disorders, anemia, asthma, obesity, paralysis, and pain. [12][13][14] Previous reports have shown that O. turpethum possesses hepatoprotective, antiulcer, antidiabetic, and anti-inflammatory activities. 13,15,16 This study was aimed at the evaluation of the analgesic and antioxidant activities of the methanolic extract of O. turpethum in mice.…”
Section: -10mentioning
confidence: 99%
“…A number of physiological entities, such as acetylcholine, histamine, substance P, cholecystokinins, prostaglandins and 5-hydroxytryptamine have been proposed as mediators of this action. Release of these chemical mediators within the gut is known to increase cytosolic calcium, which in turn stimulates intestinal propulsion (Rehman et al, 2012;Shareef et al, 2014). The presence of phyto-constituents such as flavonol, phenolics and alkaloids are also reported to be responsible for laxative activities found in various plants (Longanga Otshudi et al, 2000;Yang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Administration of Aa.Cr at higher doses of 30, 100, 300, and 700 mg/kg caused protection against experimentally induced diarrhea in mice, similar to the standard antidiarrheal drug, loperamide. Mice are commonly used to study gastrointestinal effects of experimental drugs in vivo (Shareef et al ., )…”
Section: Discussionmentioning
confidence: 99%
“…Rats, anesthetized with sodium thiopental (Pentothal, 80–100 mg/kg, i.p. ), underwent endotracheal intubation followed by ventilation with a volume ventilator (miniature ideal pump, Bioscience, UK) adjusted at a rate of 70–80 strokes/min to deliver 7–10 ml/kg of room air (Shareef et al ., ). A polyethylene catheter was inserted into the jugular vein for drug administration.…”
Section: Methodsmentioning
confidence: 97%